Mechatronics educational systems in vibration field. Issue 1 (December 2020) - Niţă, E; Comeagă, D; Avram, M
Abstract: This paper presents a set of didactic applications in order to highlight the phenomena of mechanical vibration, the modal forms of the vibration, the resonance frequency and the methods of vibration damping, passive and semi-active or active. The approach is optimized for the field of mechatronics, describing the behavior of the systems using a mathematical formalism that allows integration into complex mechatronic models. Dynamic response control solutions are also developed from a mechatronic point of view, optimizing the transfer and the response functions. First example of an educational mechatronic system is a steel beam with a diameter of 6mm, with one end fixed on an aluminum plate. When an electrical signal control is applied, an electromagnet stretches a steel wire fixed between the free end of the beam and the movable part of the electromagnet. Another example of an application in the field of mechanical vibration is a metal beam fixed in several ways (fixed at one end, fixed at both ends and with hinged fastening, on a fixed support). The beam oscillates due to a couple of actuators (each connected to a signal generator and to an amplifier), one used to produce a primary vibration in the beam and the other one to produce a secondary vibration that must interfere with the first one in order to reduce it. The aim of this application is to present to the students the phenomenon of mechanical vibration, the role played by the frequency of the vibration wave, the vibration modes existing for this given situations, but also to highlight the excitation of the metallic structures in the magnetic field, used especially for vibrations control applications. The stand also demonstrates the possibility of active vibration control of distributed systems.